Tinjauan Siyasah Maliyah Tentang Pengawasan Keuangan Negara Melalui Opini Wajar Tanpa Pengecualian oleh Badan Pemeriksa Keuangan - Al Haura Millani; Beni Ahmad Saebani; Chaerul Shaleh (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
An Unqualified Opinion is one of the prestigious achievements sought by government officials who use public funds in the performance of their duties. An Unqualified Opinion is not the sole indicator of sound financial management, nor does it guarantee freedom from corruption. This study aims to examine whether the Unqualified Opinion aligns with the objectives of oversight and the principles of fiscal policy in efforts to achieve sound financial governance and advance the public interest. Data were collected through a literature review using content analysis, which involves analyzing the content and interpreting various legal provisions and relevant concepts to address the research questions. The results of the study indicate that the unqualified audit opinion (WTP) is fundamentally consistent with the principles of fiscal policy, particularly the principle of trust and the objectives of state financial oversight in safeguarding public assets. Nevertheless, the WTP opinion cannot serve as an absolute guarantee that an entity is free from corruption due to the limited scope of the audit and the nature of financial statement examinations, which are not specifically designed to uncover acts of corruption. Nevertheless, the unqualified opinion (WTP) retains strategic value as an instrument of state financial oversight because it plays a preventive role in enhancing accountability, minimizing the potential for irregularities, and supporting the realization of good governance.